PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATA PELAJARAN MATEMATIKA BERBASIS MODEL PROBLEM BASED LEARNING (PBL) DI KELAS 2 SEKOLAH DASAR - Fifin Nabawiyah; Salmaini Salmaini; Syafri Ahmad (STKIP Subang, 2025)
This research on the development of student worksheets (LKPD) for mathematics aims to address the difficulties faced by students in learning to recognize shapes around us in grade 2. Based on these conditions, the purpose of this study is to develop teaching materials in the form of Student Worksheets (LKPD) designed using the Problem-Based Learning (PBL) model for the mathematics subject of shapes around us in grade 2. The type of research used is Research and Development (R&D), with a 4D development model. This model consists of four main stages: the Define stage to determine and define the requirements needed for the lesson; Design to design the concept and content of the LKPD; Development to create and validate the product; and Dissemination to test the effectiveness of using this learning media. In the LKPD validation stage, the assessment was carried out by three validators consisting of a module expert, a language expert, and a media expert. Based on the validation results, the process involved validation of teaching modules (82.5% valid category), language (90.6% very valid), and media (86.1% valid), followed by trials with 21 students using shape recognition activities, group discussions, LKPD, and presentations. Based on all validation results, it can be concluded that the developed Student Worksheet (LKPD) is suitable for use in second-grade mathematics learning in elementary schools. This LKPD is not only valid but also effective in improving student learning outcomes. In addition, it also serves as additional teaching material for elementary school teachers.